A First Look into the Corpus of Humanist "Laudationes Urbis" on the Eastern Adriatic Coast - Jovanović, Neven, filolog (2010)
Latin praises of a city were widely popular during the Renaissance and important not only for their authors, but also for the place praised, whose self image the praise helps shape or confirm. Such praises were written by humanists for several Dalmatian cities (Kotor, Dubrovnik, Split, Trogir, Šibenik). Some are just obiter dicta, others are the central theme of a text. Authors were both visitors (Ciriaco d'Ancona, Michele Marullo Tarcaniota, Didacus Pyrrhus, Filippo Diversi, Palladio Fosco) and locals (Ivan Bolica, Marko Marulić, Frano Božićević Natalis, Ivan Lipavić, Vinko Priboević, Juraj Šižgorić). Their texts constitute now a digital corpus Laudationes urbium Dalmaticarum, included in a digital collection Croatiae auctores Latini (2009). In the sub-corpus of laudationes we research the following: What did the authors choose to say about these cities? How did they say it? How does it comply with motifs and forms of other humanist laudationes urbium / laudationes civitatum?
Projekt MZOS
ENG